7-(6-Bromohexyloxy)-4-methyl-2H-chromen-2-one - Hui-Zhen Zhang; Qing-Xia Li; Ben-Tao Yin; Cheng-He Zhou (Acta Crystallographica Section E, 2012)
In the title molecule, C16H19BrO3, all non-H atoms apart from the Br atom are approximately coplanar, with a maximum deviation of 0.242 (4) Å. The C—C—C—Br torsion angle is 66.5 (4)°.